2021
DOI: 10.3390/en14102746
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Evaluation of Non-Toxic Jatropha curcas in Rural Marginal Soil for Obtaining Biodiesel Using Life-Cycle Assessment

Abstract: Using information from an experimental planting of non-toxic Jatropha curcas (NTJC) with minimal water and fertilization resources on rural marginal soil the objective of this article is to determine the sustainability of this raw material for producing biodiesel and the possibilities for improving it through life-cycle assessment (LCA). Three production scenarios were studied: minimal resources (MR), which focuses on the obtaining of biodiesel; minimal resources and utilization of sub-products (MRUS), which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…In a BRF, bioenergy, biofuels, chemicals, and biomaterials are produced by integrating several technologies and processes [10,44]. Food and fiber are sometimes obtained, depending on the raw material and process combination within the BRF [8,45]. The different types of biomass and processes used in BRFs include lignocellulosic biomass and organic waste [9,11].…”
Section: General Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In a BRF, bioenergy, biofuels, chemicals, and biomaterials are produced by integrating several technologies and processes [10,44]. Food and fiber are sometimes obtained, depending on the raw material and process combination within the BRF [8,45]. The different types of biomass and processes used in BRFs include lignocellulosic biomass and organic waste [9,11].…”
Section: General Contextmentioning
confidence: 99%
“…BRFs use different types of biomass as raw materials, such as solid organic waste, lignocellulosic biomass, and algae. Depending on their configurations, these BRFs can produce a range of biofuels, such as ethanol, biodiesel, methane, hydrogen, synthesis gas, electricity/heat, and bio-oil [8][9][10][11]; these biofuels generate lower GHG emissions than fossil fuels, which also offer critical environmental benefits. Palandri et al [12] reported that ethanol and biodiesel emit up to 80% less CO 2 -equivalent (CO 2 e) emissions when produced with organic waste than gasoline or diesel.…”
Section: Introductionmentioning
confidence: 99%